Effects of Late-Summer Prescribed Fire on Botanical Composition, Soil Cover, and Forage Production in Caucasian Bluestem-Infested Rangeland in the Kansas Smoky Hills: Year 4 of 5 - H. P. Giefer; K. R. Harmoney; M. P. Ramirez; A. J. Tajchman; Z. M. Duncan; J. Lemmon; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:Our objective was to determine effects of late-summer prescribed fire on frequency of Caucasian bluestem (Bothriochloa bladhii) in the Kansas Smoky Hills as well as changes in soil cover, botanical composition, and forage production associated with fire treatment. Study Description:The study was in Ellsworth County, KS. Eighteen one-acre plots were randomly assigned to one of three treatments: no burn, one burn (August 14, 2019), and two burns (August 14, 2019, and August 11, 2021). Soil cover, botanical composition, forage production, and Caucasian bluestem frequency were measured annually beginning in 2019. The Bottom Line:These data suggest that regular application of late-summer prescribed fire may be an effective method to reduce Caucasian bluestem frequency while improving overall grass-species richness.
Keywords: botanical composition; old-world bluestems; prescribed burning